Rethinking the American prison movement - Berger, Dan (American social and political movements of the twentieth century, 2018)
Introduction -- Roots: challenging prison slavery and political repression, 1865-1940 -- Rights: fighting prison Jim Crow, 1940-1968 -- Revolution: the prison rebellion years, 1968-1972 -- Radicalism: unions, feminism, and the crisis of prison managerialism, 1973-1980 -- Retrenchment: mass incarceration and the remaking of the prison movement, 1980-1998 -- Conclusion